Current topics in membranes. - Bennett, Vann (Current topics in membranes, 2013)
This volume covers recent breakthroughs in understanding the molecular and cellular basis for patterning vertebrate plasma membranes. A special emphasis is placed on physiological function with chapters covering signaling in the nervous system and heart, vision, and the immune system.